Azid-chemical recycling of plastics a feasibility study - Dagdag, Kristel R.; Fabula, Selina Irish F.; Macabali, Kristine Nicole M.; Romero, Maria Rosa M. (College of Engineering, 2013)
AZID is a 889 sq. m plastic recycling facility to be located in Valenzuela City. Unlike most of the plastic recycling facilities that use heat to recycle plastic waste, AZID uses nitric acid to degrade the plastic into its monomer form and then to its resin form. This resin will then be sold to plastic manufacturers in the country that utilize recycled plastic resin for their products. AZID, unlike any other existing recycling facility, will recycle both thermoplastics and thermosets through its new technology on chemical recycling, focusing on five different kinds - polyethylene, polystyrene, polypropylene, polyvinyl chloride and the thermosets. A yearly forecast sales of more than 8,000 MT of resin is expected at minimum for the next five years. This results to a yearly revenue of more than Php 150,000,000.00. With a start-up cost of Php 54,827,626.20 and an expected initial financing of Php 60,075,000 (65% from loan and 35% from shares), the facility is expected to produce 12,800 kg of resin daily. The facility will be under a 2-shift daily production, employing at least 28 machine operators and 17 other workers. On its first year of operation, AZID's net income is expected to already be positive which means the company can already compensate its operational expenses. The payback period is also estimated to be around 4.03 years. Additionally, financial projections also show an IRR of 29% and NPV of Php 38,980,847 which are good figures for an investment. Being a recycling facility, AZID aims to help the country through its waste management. The facility is expected to contribute Php 6,318,000.00 to the environment in terms of monetary value. Also, the facility aims to contribute to the community by providing additional jobs and the government through taxes. All in all, AZID is a technically feasible recycling facility, and through its promising market, is expected to be viable and profitable in the long run.